From Peace and The Planetary Republics of the Century of Lights to the Materialization of Perpetual Peace and Universal Citizenship. / De la paz y las repúblicas planetarias del siglo de las luces a la materialización de la paz perpetua y la ciudadanía universal. - ARRIETA-LÓPEZ, Milton (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In this article, the author examines the relationship between the integration of people and peace from the perspective of the planetary republics of the century of lights and the consolidated experiences of the United States and the European Union. The methodology use is a documentary and bibliographical review and critical analysis, through which the author discusses the evolution of integrationist ideas related to peace and to the possibilities of its universalization through public international law. The main conclusion is that the consolidated experiences show that the harmonious integration of nations entails the foundations of perpetual peace. RESUMEN Se examina la relación entre la integración de los pueblos y la paz desde la perspectiva de las repúblicas planetarias del siglo de las luces y de las experiencias consolidadas de Estados Unidos y la Unión Europea. La metodología empleada es la revisión documental, bibliográfica y el análisis crítico, mediante la cual se diserta sobre la evolución de las ideas integracionistas relacionadas con la paz hasta las posibilidades de su universalización a través del derecho internacional público. Se concluye principalmente que las experiencias consolidadas demuestran que la integración armónica de los pueblos conlleva los fundamentos de la paz perpetua.